A common single nucleotide polymorphism A118G of the μ opioid receptor alters its N-glycosylation and protein stability - Huang, Peng; Chen, Chongguang; Mague, Stephen D; Blendy, Julie A; Liu-Chen, Lee-Yuan (Biochemical journal, 2012)
The A118G SNP (single nucleotide polymorphism) of the hMOPR [human MOPR (μ opioid receptor)] gene OPRM1 results in an amino acid substitution (N40D). Subjects homozygous for the 118G allele have been reported to require higher morphine doses to achieve adequate analgesia, and the 118G allele is more prevalent among drug abusers. However, changes in the MOPR protein associated with this SNP are unknown. Using a knockin mouse model (G/G mice; mice homozygous for the 112G allele of MOPR) that possesses the equivalent nucleotide/amino acid substitution (A112G; N38D) of the A118G SNP in the hMOPR gene, we investigated the N-linked glycosylation status of thalamic and striatal MOPR in G/G mice compared with A/A mice (wild-type mice homozygous for the 112A allele of MOPR). The molecular mass of MOPR determined by immunoblotting was lower in G/G mice than in A/A mice. Following treatment with peptide N-glycosidase F, which removes all N-linked glycans, both MOPR variants had an identical molecular mass, indicating that this discrepancy was due to a lower level of N-glycosylation of the MOPR in G/G mice. In Chinese-hamster ovary cells stably expressing hMOPRs, 118G/Asp40-hMOPR had a lower molecular mass than 118A/Asn40-hMOPR, which was similarly due to differential N-glycosylation. Pulse-chase studies revealed that the half-life of the mature form of 118G/Asp40-hMOPR (~12 h) was shorter than that of 118A/Asn40-hMOPR (~28 h). Thus the A118G SNP reduces MOPR N-glycosylation and protein stability.